A QUR'AN-BASED VALUE LEARNING MODEL: STRENGTHENING SPIRITUAL CHARACTER IN ISLAMIC EDUCATION - Saparuddin, Saparuddin; Sudirman, Sudirman; Al-Ayyubi , Muh. Salahuddin (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study is grounded in the theoretical framework of Value-Based Learning (VBL) and Islamic education philosophy, which emphasize the integration of Qur’anic values into learning as a means of developing holistic spiritual character. Purpose: This research aims to examine how Qur’an-based VBL influences students’ spiritual intelligence and moral behavior. Method: Using a qualitative descriptive approach, data were collected from 25 students at Universitas Islam Makassar through in-depth interviews and analyzed using content analysis to identify relevant themes and categories. Result: The findings reveal that the implementation of Qur’an-based VBL enhances students’ awareness of worship, strengthens their faith, and cultivates honesty, responsibility, and social care. The five stages of VBL orientation, internalization, application, reflection, and habituation serve as practical strategies for teachers to transform Qur’anic values from knowledge into habitual character. Conclusion: This study contributes theoretically by enriching the discourse on Qur’an-based value education and practically by offering a structured model for Islamic educators to integrate spiritual and moral development into classroom practices, thereby reinforcing the transformative role of Islamic education in the modern era.